Website Desa sebagai Media Inovasi Desa di Desa Bernung Kabupaten Pesawaran Provinsi Lampung - Simon Sumanjoyo Hutagalung; Dedy Hermawan; Nana Mulyana (Jurnal Pengabdian Pada Masyarakat, 2020)
VILLAGE WEBSITE AS INNOVATION MEDIA IN BERNUNG VILLAGE, PESAWARAN REGENCY, PROVINCE OF LAMPUNG. The urgent problem in the management of the village government website in Pesawaran Regency, Lampung Province is the quality aspect of service management and its use as a tourism promotion media. More specifically, these conditions are related to two aspects as follows; (1). Human resources, especially in terms of the capacity and quality of village officials and village government website managers, and (2). Institutional, especially in the availability of work guidelines and evaluation tools for village government website management. The method of implementation is carried out using the principle that every innovation received by partners should go through a process, listening, knowing, trying, evaluating, accepting, believing, and implementing. So that every process goes well, the delivery of innovations to Partners is carried out through the stages of explanation, discussion, practice and mentoring. At the end of the activity, it was concluded that the concept of village website management was understood, the process and mechanism of village website management as well as the importance of the active role of the village apparatus in the management of village website management by the village apparatus in Desa Bernung, Pesawaran Regency. Based on this it can be concluded if there has been increased knowledge and understanding of the Village Apparatus in terms of managing the village Website as a village innovation media.